2010
DOI: 10.1016/j.juro.2010.06.147
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette-Guérin With or Without Interferon α-2b and Megadose Versus Recommended Daily Allowance Vitamins During Induction and Maintenance Intravesical Treatment of Nonmuscle Invasive Bladder Cancer

Abstract: Interferon α-2b added to bacillus Calmette-Guérin induction and maintenance intravesical therapy did not decrease tumor recurrence in bacillus Calmette-Guérin naïve cases, but was associated with increased fever and constitutional symptoms. No difference in time to recurrence was present in patients receiving recommended daily allowance vs high dose vitamins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 30 publications
2
61
0
Order By: Relevance
“…The authors reported a comparable recurrence rate for patients with BCG failure after 12 months of remission relative to BCG naïve patients. Similarly, Nepple et al [22] found no difference in terms of recurrence-free survival after a 24-month median follow-up; when IFNα and daily allowance vitamins were added to maintenance treatment with BCG (63% vs. 55%, p>0.05) in a prospectively randomized trial. Accordingly, adding IFNα to BCG does not improve the oncological outcomes of the patients.…”
Section: Interferon 2αmentioning
confidence: 88%
“…The authors reported a comparable recurrence rate for patients with BCG failure after 12 months of remission relative to BCG naïve patients. Similarly, Nepple et al [22] found no difference in terms of recurrence-free survival after a 24-month median follow-up; when IFNα and daily allowance vitamins were added to maintenance treatment with BCG (63% vs. 55%, p>0.05) in a prospectively randomized trial. Accordingly, adding IFNα to BCG does not improve the oncological outcomes of the patients.…”
Section: Interferon 2αmentioning
confidence: 88%
“…For example, BCG has been combined with type I IFN, with the aim of enhancing TRAIL expression on innate immune cells. 39,40 Herein, we established a mathematical model to evaluate the capacity of the innate immune system to mediate the observed tumor immunity in patients receiving BCG therapy for their bladder cancer. Importantly, the model accurately reflected the recruitment and activation of innate immune cells during the 6-week course of BCG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…70,72 By con trast, the only randomized study of the combination of BCG with IFNα2b in BCGnaive patients failed to demonstrate any superiority of the combination over BCG alone, even though the tolerability of reduced dose BCG-IFNα2b seemed to be better than that of fulldose BCG alone. 73 Nevertheless, the lack of RCTs and lack of superiority of BCG-IFN versus BCG alone in BCGnaive patients has limited the widespread use of this combination treatment. Furthermore, even this therapy has unsatisfactory activity in BCGrefractory patients.…”
Section: Options After Bcg Failurementioning
confidence: 99%